Rethinking Terence: a metrical and musical study of Andria (Argos, 2023)
This paper proposes a metrical analysis of Terence’s Andria based on a deviation from the traditional way of studying Terence’s works —which judges them by Plautus’ compositional methods—, in order to study Terence’s metrical features altogether. The analysis of the comedy’s metrical macrostructure and microstructure shows a deep interweaving of metrical and musical components with the meaning of the plot elements and sheds light on the composition and the functions of cantica.
Keywords: Terence; Andria; Metrics; Performance; Ludus